Enrichment of patchouli alcohol in extracted patchouli oil from Pogostemon cablin benth leaves using supercritical carbon dioxide - Wahyudiono; Ajeng Almira Tarisha Asri; Pramudya Riandana Bhayu Gautama; Sugeng Winardi; Tadafumi Adschiri; Motonobu Goto; Siti Machmudah (Case Studies in Chemical and Environmental Engineering)
Essential oil has been extensively applied in various industrial applications for different purposes. In this work, essential oil from the cultivated Pogostemon cablin Benth in Malang, Indonesia was extracted by supercritical carbon dioxide (CO2) method. The experiments were carried out in a semi batch-type process at various operating conditions (40−80 °C of temperatures and 10−20 MPa of pressures). The extraction time was 120 min, while the CO2 flow rates were 3–5 mL/min. The gas chromatography mass spectrometry (GC-MS) indicated that the extracted patchouli oil comprises patchouli alcohol as a main substance. The results indicated that the supercritical CO2 extraction method is to be superior compared with the hydrodistillation extraction method. By hydrodistillation extraction method, the extracted patchouli oil was around 0.52 %, while by supercritical CO2 extraction method, the extraction yield increased significantly to 3.04 %. Besides the high extraction yield, the supercritical CO2 extraction method also can give a high quality of patchouli oil extract.